Evaluate the Association of Various Electrolyte Abnormalities with Preeclampsia - Shahida Malik, Sabiha Riaz, Nargis Gulab, Komal Zahra, Amreen Khan, Nuzhat Sultana (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Preeclampsia is a complex hypertensive disorder of pregnancy characterized by new-onset hypertension and proteinuria or significant end-organ dysfunction after 20 weeks of gestation. Objective: The main objective of the study is to find the association of various electrolyte abnormalities with preeclampsia. Methodology: This cross-sectional study was conducted at Department of Gynecology DHQ Hospital Killa saifullah during December 2021 to October 2022. A study was conducted on 165 patients diagnosed with preeclampsia. Patients were selected based on clinical and laboratory criteria, including blood pressure measurements, proteinuria, and relevant electrolyte profiles. Results: Women with severe preeclampsia were diagnosed at an earlier gestational age (31.3 ± 2.9 weeks) compared to those with mild preeclampsia (33.2 ± 2.7 weeks) (p = 0.013). Systolic and diastolic blood pressures were significantly higher in the severe preeclampsia group (161.3 ± 9.7 mmHg and 106.5 ± 8.4 mmHg, respectively) compared to mild cases (145.8 ± 8.5 mmHg and 93.6 ± 7.1 mmHg) (p < 0.001). Additionally, proteinuria levels were markedly elevated in severe preeclampsia (2.1 ± 0.7 g/day) compared to mild cases (0.8 ± 0.3 g/day) (p < 0.001). Conclusion: It is concluded that electrolyte imbalances, particularly reduced levels of calcium, magnesium, and potassium, along with elevated phosphate levels, are significantly associated with the severity of preeclampsia. Keywords: Preeclampsia, Calcium, Magnesium, Potassium